Sense and practices of fatherhood: voices of young men in deprivation of liberty (Polis (Santiago), 2018)
The reflections presented here are part of a cartographic research on gender and sexuality in the Socio-educational System of Rio de Janeiro from 2015-2017. From individual interviews, group activities and courses with young people and professionals, this paper discusses the various meanings that the experience of paternity has for young fathers in deprivation of liberty, connecting them to the production of masculinities in the trajectories of the youngsters, circumscribed in codes of institutions such as drug trafficking groups and the Socioeducational System itself. Considering the context of social, racial, generational, and gender inequality, we explore how capitalist subjectivity shapes practices and power relations in what we might call ostentation-paternity.
Keywords: fatherhood; young men deprived of liberty; masculinities.